A Semiotic Analysis of the Hafalan Shalat Delisa Movie Using Charles Sanders Peirce’s Semiotic Theory - Rahmaton Rahmaton; Dohra Fitrisia; Chai Nasir (Research in English and Education Journal, 2023)
This research was about the film of Hafalan Shalat Delisa movie. Hafalan Shalat Delisa movie is an Indonesian drama film released on December 22th , 2011. This film is based on the bestselling novel by Tere Liye with the same title “Hafalan Shalat Delisa”. All of the film’s scenes were shot in Aceh. This research which aims to explore the kind of signs that are expressed and to analyzed the meaning of the three important elements of signs including icons, indexes, and symbols found in the film. This research was descriptive qualitative method using a semiotic theory who advocated by Peirce as its theoretical framework. The data from this research were collected of using note taking. The analysis of  meaning revealed three elements of signs could indeed be interpreted using Peirce’s semiotic theory, especially the relationship between their object (O), representamen (R), and interpretant (I). The data found on Hafalan Shalat Delisa movie was 13 signs which are, four of icons, four of indexes and five for symbols. Based on the result of study, using Peirce’s theory can describe the meaning of the movie and the message to the audience.